2020
DOI: 10.3390/urbansci4030039
|View full text |Cite
|
Sign up to set email alerts
|

Urban Commute Travel Distances in Tehran, Istanbul, and Cairo: Weighted Least Square Models

Abstract: A very large part of the literature on urban commute travels is related to high-income countries. The determinants of urban commute trip distances are not clear in the Middle East and North Africa (MENA); thus, this study attempts to shed light on this topic in relation to Tehran, Istanbul, and Cairo. The objective is to clarify which environmental and human factors are correlated with commuting distance in these cities. Using primary disaggregate data produced by surveys in the three cities (n = 8237) in 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Our results show that with longer streets around workplaces, people use active forms of mobility less in their commutes, which is in line with another investigation on mode choices in the Middle East and North Africa (MENA) [58]. The findings of our paper regarding a positive correlation between street-length density around homes and commuting distance confirm similar results as those of another MENA city, Tehran [59].…”
Section: Discussionsupporting
confidence: 91%
“…Our results show that with longer streets around workplaces, people use active forms of mobility less in their commutes, which is in line with another investigation on mode choices in the Middle East and North Africa (MENA) [58]. The findings of our paper regarding a positive correlation between street-length density around homes and commuting distance confirm similar results as those of another MENA city, Tehran [59].…”
Section: Discussionsupporting
confidence: 91%
“…The variable is significant for Cairo and Istanbul, and marginally significant in Tehran [30]. In another study, it has been shown that household car ownership is a highly significant predictor of commuting distance in a cumulative sample of Istanbul, Tehran and Cairo [31]. Nevertheless, as said above, no consistent and comprehensive results about car ownership predictors in the region are available.…”
Section: Literature Review 21 Car Ownershipmentioning
confidence: 91%
“…In addition, we generally know that a destination being far away, as an indicator of accessibility, is the most powerful element against walking in the large cities of the MENA region [22]. In such cities, the walking distance to the neighborhood amenities and also the number of neighborhood amenities located in the catchment area of homes are significant determinants of several travel behaviors, including making the trip for both commute and non-commute travels [23], and the commuting distances [24]. Walkable distance to neighborhood facilities and also the number of accessed facilities are also highly significantly correlated with whether or not people in Tehran, Istanbul, and Cairo choose their residential location based on mobility needs [25].…”
Section: Introductionmentioning
confidence: 99%